2010
DOI: 10.1111/j.1540-8167.2010.01942.x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Navigation in Catheter Ablation for Paroxysmal Atrial Fibrillation: Midterm Efficacy and Predictors of Postablation Arrhythmia Recurrences

Abstract: This study demonstrates feasibility and safety of robotic navigation in catheter ablation for paroxysmal AF. Midterm follow-up documents success rate comparable to other technologies and potential for improvement in more extensive ablation along the ridges with thicker myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…In a previously published study, is was shown that left atrial mapping and PVI with the RCS is feasible and effective. No major complication was observed 7 , confirming previously published results on the safety of robotic ablation 12,13 . Operator fluoroscopy exposure is significantly lower without decrease of procedural success rates 7 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a previously published study, is was shown that left atrial mapping and PVI with the RCS is feasible and effective. No major complication was observed 7 , confirming previously published results on the safety of robotic ablation 12,13 . Operator fluoroscopy exposure is significantly lower without decrease of procedural success rates 7 .…”
Section: Discussionsupporting
confidence: 79%
“…Advance a circular mapping catheter via the long sheath into the LA (circular mapping catheter shown in Figure 2B). 13. Perform a 3-D anatomical reconstruction of the LA with the use of a mapping system and the circular mapping catheter.…”
Section: Pre-ablation Preparationmentioning
confidence: 99%
“…Special catheters with magnets affixed to their distal end can be navigated PV isolation reports in paroxysmal and persistent AF patients using the Sensei system have consistently shown significant shortening of the fluoroscopy time. [48][49][50][51][52] Remote isolation of the PV showed similar midterm follow-up (six-months to one-year) free of atrial arrhythmias to manual point-by-point radiofrequency delivery. Without adjunctive antiarrhythmic drugs ≈70 % of paroxysmal AF patients remained free of atrial arrhythmias.…”
Section: Pulmonary Vein Isolation By Remote Navigationmentioning
confidence: 92%
“…Without adjunctive antiarrhythmic drugs ≈70 % of paroxysmal AF patients remained free of atrial arrhythmias. [50][51][52] Initial reports using the Sensei system had raised the concern of higher rate of cardiac tamponade than conventional manual RF delivery 53 , which might be related to remote manipulation of the stiff steerable Artisan catheter (Hansen Medical, Mountain View, CA, US). Further experience and introduction of a special feature of the system to indirectly estimate catheter contact force on the tissue (IntelliSense) have shown that tamponade rates are not greater than the conventional manual approach and may be more related to different temperature and power RF settings.…”
Section: Pulmonary Vein Isolation By Remote Navigationmentioning
confidence: 99%
“…Further experience and introduction of a special feature of the system to indirectly estimate catheter contact force on the tissue (IntelliSense) have shown that tamponade rates are not superior to conventional manual approach and may be more related to different temperature and power radiofrequency settings. 20 The CGCI system does not require a lab with specific magnetic isolation since the magnetic field is highly focused on patient's torso. In addition, the electrophysiology room can be used either as a conventional electrophysiology lab or as a magnetic lab by moving patient's table from its regular position towards the magnetic chamber.…”
Section: Discussionmentioning
confidence: 99%